Lessons Learned from Sudan Ebola Virus Disease (SUDV) Preparedness in Rwanda: A Comprehensive Review and Way Forward - Edson Rwagasore; Olivier Nsekuye; Ziad El-Khatib; Adeline Kabeja; Valois H. Mucunguzi; Pacifique Nizeyimana; Edward Ruseesa; Laurent Ruyange; Isabelle B. Teta; Sandrine Uwamahoro; Solange Twahirwa; Denyse Mugawaneza; et al. (Springer, 2023)
Abstract Background Ebola Virus Disease (EVD) is a severe and often fatal illness that affects humans and has significant public health implications, including high mortality rates, strain on healthcare systems, and social and economic disruption. On 20 September 2022, Uganda declared an Ebola disease outbreak caused by the Sudan ebolavirus species. The neighboring countries of Uganda were classified by World Health Organization (WHO) as being at high risk of Sudan Ebola Virus Disease (SUDV) importation. The country of Rwanda implemented different sustainable strategies and activities to prepare and ensure a timely and effective response to SUDV outbreaks once it has arrived in the country. We aimed to highlight the sustainable strategies and activities implemented for SUDV preparedness and the subsequent lessons learnt in Rwanda. Methods This paper reviewed the documentation on activities implemented for SUDV preparedness, with a focus on lessons learned from different countries. The paper analyzed the common themes and highlighted the key components of EVD preparedness in Rwanda after declaration of SUDV outbreak in Uganda. Results The key components of SUDV preparedness include its readiness assessment in Rwanda, effective coordination, collaboration and leadership mechanisms, enhancing the early detection and surveillance system, effective risk communication and community engagement, capacity building of healthcare providers on case management and infection prevention and control (IPC), and continual preparedness. These components were essential to ensure timely and effective preparation and response to SUDV related outbreaks. Conclusion A multi-sectoral approach involving all stakeholders was necessary to ensure timely and effective preparation and response. Continuous investment in preparedness, strengthening of health systems, and the review of preparedness components provided insights into the best practices for SUDV preparedness, which were essential to prevent future outbreaks and minimize their impact. This will inform other countries about the role of timely development of preparedness plans.